Head Start Immunity: Characterizing the Early Protection of C Strain Vaccine Against Subsequent Classical Swine Fever Virus Infection - McCarthy, Ronan R.; Everett, Helen E.; Graham, Simon P.; Steinbach, Falko; Crooke, Helen R. (Frontiers in Immunology, 2019)
Classical Swine Fever Virus (CSFV) is an ongoing threat to the pig industry due to its high transmission and mortality rates associated with infection. Live attenuated vaccines such as the CSFV C strain vaccine are capable of protecting against infection within 5 days of vaccination, but the molecular mechanisms through which this early protection is mediated have yet to be established. In this study, we compared the response of pigs vaccinated with the C strain to non-vaccinated pigs both challenged with a pathogenic strain of CSFV. Analysis of transcriptomic data from the tonsils of these animals during the early stages after vaccination and challenge reveals a set of regulated genes that appear throughout the analysis. Many of these are linked to the ISG15 antiviral pathway suggesting it plays a key role in the rapid and early protection conferred by C strain vaccination.